Effects of Soybean Lecithin on Growth Performance, Intestine Morphology, and Liver Tissue Metabolism in Rock Bream (Oplegnathus fasciatus) Larvae - Tan, Peng; Zhang, Pian; Zhang, Lei; Zhu, Wenliang; Wang, Ligai; Chen, Ruiyi; Zhu, Qihui; Xu, Dongdong (Frontiers in Marine Science, 2022)
This study aimed to investigate the effects of dietary soybean lecithin (SL) inclusion in rock bream (Oplegnathus fasciatus) larvae on growth performance, liver metabolism, hypoxia stress, and potential molecular mechanisms. Four types of equal-protein and equal-lipid content microdiets (MDs) were formulated with graded levels of soybean lecithin to achieve phospholipid levels of (PLs, dry matter) 3.84% (SL0), 6.71% (SL4), 9.38% (SL8), and 12.21% (SL12). Rock bream larvae (25 days post-hatching) were fed the respective MDs for 30 days with three replicates. We found that dietary soybean lecithin inclusion promoted growth performance, survival rate, and stress resistance to hypoxia stress. The growth promotion by increased dietary soybean lecithin inclusion could be attributed to the improvement of the intestinal structure, as shown by the increased perimeter ratio, muscular thickness, and mucosal fold height of the mid-intestinal tissue. Moreover, a high soybean lecithin inclusion diet increased liver tissue lipolysis-related key enzyme (lipase [LP]) activity but decreased amino acid catabolism-related enzyme (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]) activities. Liver tissue RNA sequencing revealed that the SL12 diet increased fatty acid activation-related gene (acsl6 and acsbg2), phospholipid catabolism (acat2, lpin2, and crls), and amino acid synthesis-related gene (gs, csb, aldh18a1, and oct) expression but decreased amino acid catabolism-related gprt2 expression. Notably, the SL12 diet significantly increased the expression of ribosome biogenesis-related genes (pes1, nop56, nop58, and rpf2) in liver tissue. The ribosome protein-related pathways were the most enriched pathways mapped in the GO database. Collectively, the findings of this study demonstrated the necessity of dietary soybean lecithin for survival, growth performance, promotion of mid-intestinal morphology, and hypoxia stress during the rock bream larval stage. The SL-induced growth performance promotion was likely attributed to increasing nutrient acquisition by intestinal morphology improvement and to increasing SL catabolism and thereby sparing amino acids for protein synthesis.